Clinical, geographical, and temporal risk factors associated with presentation and outcome of vivax malaria imported into the United Kingdom over 27 years: observational study. (16th April 2015) - Broderick, Claire; Nadjm, Behzad; Smith, Valerie; Blaze, Marie; Checkley, Anna; Chiodini, Peter L; Whitty, Christopher J M
Abstract : Objective To examine temporal and geographical trends, risk factors, and seasonality of imported vivax malaria in the United Kingdom to inform clinical advice and policy. Design Observational study. Setting National surveillance data from the UK Public Health England Malaria Reference Laboratory, data from the International Passenger Survey, and international climactic data. Participants All confirmed and notified cases of malaria in the UK (n=50 187) from 1987 to 2013, focusing on 12 769 cases of vivax malaria. Main outcome measures Mortality, sociodemographic details (age, UK region, country of birth and residence, and purpose of travel), destination, and latency (time between arrival in the UK and onset of symptoms). Results Of the malaria cases notified, 25.4% (n=12 769) were due to Plasmodium vivax, of which 78.6% were imported from India and Pakistan. Most affected patients (53.5%) had travelled to visit friends and relatives, and 11.1% occurred in tourists. Imported P vivax is concentrated in areas with large communities of south Asian heritage. Overall mortality was 7/12 725 (0.05%), but with no deaths in 9927 patients aged under 50 years. Restricting the analysis to those aged more than 50 years, mortality was 7/2798 (0.25%), increasing to 4/526 (0.76%) (adjusted odds ratio 32.0, 95% confidence interval 7.1 to 144.0, P<0.001) in those aged 70 years or older. Annual notifications decreased sharply over the period, while traveller numbers between the UK and South Asia increased. The risk of acquiring P vivax from South Asia was year round but was twice as high from June to September (40 per 100 000 trips) compared with the rest of the year. There was strong seasonality in the latency from arrival in the UK to presentation, significantly longer in those arriving in the UK from South Asia from October to March (median 143 days) versus those arriving from April to September (37 days, P<0.001). Conclusions Travellers visiting friends and family in India and Pakistan are most at risk of acquiring P vivax, and older patients (especially those >70 years) are most at risk of dying; these groups should be targeted for advice before travelling. The risk of acquiring vivax malaria is year round but higher during summer monsoons, masked by latency. The latency of time to clinical presentation of imported vivax malaria in the UK is highly seasonal; seasonal latency has implications for pretravel advice but also for the control of malaria in India and Pakistan. A reduced incidence of vivax malaria in travellers may mean further areas of South Asia can be considered not to need malaria chemoprophylaxis.